2006
DOI: 10.1590/s0103-64402006000100016
|View full text |Cite
|
Sign up to set email alerts
|

Anatomosurgical study of the marginal mandibular branch of the facial nerve for submandibular surgical approach

Abstract: The purpose of this study was to estimate the distance from the mandibular marginal branch of the facial nerve to the inferior margin of the mandible in order to determine the best and safest location to approach the posterior mandibular region. Forty-five hemi-faces of 27 Brazilian adult cadavers were dissected and the distance between the mandibular marginal branch and the inferior margin of the mandible was measured. The number of marginal branches and anastomoses with other branches of the facial nerve was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
6

Year Published

2008
2008
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 12 publications
2
43
0
6
Order By: Relevance
“…To achieve this distance the authors propose to mark a projection of one (Dingman & Grabb) or two (Ziarah & Atkinson, 1981;Cranin, 1975;Ellis & Zide, 1995;Potgieter et al, 2005) finger width below the LBM. At the time this review was carried out, we observed other recommendations as varied as making the incision at a distance of at least 1.6 cm from LBM and Gonion (Batra et al), 2.1cm (Karapinar et al) and 3 cm or more (Wang et al;Woltmann et al;Savary et al, 1997;Kim et al, 2009;Zani et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve this distance the authors propose to mark a projection of one (Dingman & Grabb) or two (Ziarah & Atkinson, 1981;Cranin, 1975;Ellis & Zide, 1995;Potgieter et al, 2005) finger width below the LBM. At the time this review was carried out, we observed other recommendations as varied as making the incision at a distance of at least 1.6 cm from LBM and Gonion (Batra et al), 2.1cm (Karapinar et al) and 3 cm or more (Wang et al;Woltmann et al;Savary et al, 1997;Kim et al, 2009;Zani et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…The most common cause of paralysis of this nerve is due to iatrogenic damage during surgery in the mandibular or parotid regions (Batra et al;O`Brien, 2007;Toure et al, 2004;Woltmann et al, 2006). Its damage can cause salivary incontinence and aesthetic impairment due to an alteration in the balance of the musculature around the lower lip, in its lateral, downward and inversion movements (Moffat & Ramsden, 1977).…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Damaging the MMBFN can cause salivary incontinence and aesthetic impairment due to an alteration in the balance of the musculature around the lower lip, preventing lateral and downward movement and lower lip inversion. 12,13 Murr suggests that the transbuccal route is technique-sensitive and nerve injury is possible. 8 MMBFN contiguity with the safety zone determined in the current study was found in 3 of 32 triangles (9.3%).…”
Section: Discussionmentioning
confidence: 99%
“…The knowledge of these data provides surgeons with anatomic basis for future surgical strategies (Woltmann et al, 2006), avoiding lesions in the facial nerve region, wich is often prone to injuries that require interventions (Guntinas-Lichius et al, 2007). Important data can also be obtained through clinical examination, using electromyography method (Wolf et al, 2006;Armstrong et al, 2007), as many facial muscles present more than one motor unity.…”
Section: Discussionmentioning
confidence: 99%